1998
DOI: 10.1097/00005537-199803000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Up‐to‐date Report of Botulinum Toxin Type A Treatment in Patients With Gustatory Sweating (Frey's Syndrome)

Abstract: Several therapeutic approaches exist to treat gustatory sweating (Frey's syndrome) following parotidectomy. Because of the lack of effective treatment, a new therapeutic modality using botulinum toxin injections was presented previously by our group. The duration of the demonstrated positive effect was essentially unknown so far. Based on our experiences using this technique since December 1993, the purpose of this clinical investigation was to make an up-to-date report and demonstrate the duration of effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
95
0
10

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 11 publications
15
95
0
10
Order By: Relevance
“…23,35,37,38 There seems to be an agreement on the 10-mm interinjection distance and on an injection dose of 0.1 mL. The 10-mm interinjection distance is supported by the data of Shaari and Sanders 36 for neuromuscular junctions: injections 10 mm away from the motor end plate band of the rat tibialis anterior muscle are ineffective in inducing paralysis.…”
Section: Otolaryngologyhead and Neck Surgerymentioning
confidence: 67%
See 1 more Smart Citation
“…23,35,37,38 There seems to be an agreement on the 10-mm interinjection distance and on an injection dose of 0.1 mL. The 10-mm interinjection distance is supported by the data of Shaari and Sanders 36 for neuromuscular junctions: injections 10 mm away from the motor end plate band of the rat tibialis anterior muscle are ineffective in inducing paralysis.…”
Section: Otolaryngologyhead and Neck Surgerymentioning
confidence: 67%
“…In a recent publication, Laskawi et al 37 have found that the effect of botulinum toxin on gustatory sweating is rather long lasting, with an average delay to recurrence of 15 months. We have the impression that the new methods that were developed for the evaluation of gustatory sweating (and especially the ISPH method) 28 are invaluable for deciding the zones to treat and the amount of botulinum toxin that should be injected.…”
Section: Otolaryngologyhead and Neck Surgerymentioning
confidence: 99%
“…About 44% of these patients reported sweat recurrence after 15 months. On examination through Minor test, sweat recurrence rate for that period was 70.5% 17 . Kuttner et al 18 described 19 patients with severe gustatory sweating following superficial parotidectomy, treated with intracutaneous injections of botulinum toxin type A.…”
Section: Discussionmentioning
confidence: 94%
“…Laskawi et al 17 reported findings in 19 FS patients suited to single-application BT, with satisfactory results being obtained. About 44% of these patients reported sweat recurrence after 15 months.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to other indications for botulinum toxin application, e.g. hemifacial spasm, blepharospasm or Meige syndrome where the beneficial effect is mostly limited to 4 months [13], the effect of this substance on gustatory sweating lasts on average for 17.3 months (mean) [14]. The reason for the longer action in autonomic compared to neuromuscular disorders is still unknown at present.…”
Section: Discussionmentioning
confidence: 96%